What are the stones whispering?: Ramat Raḥel : 3000 years of forgotten history - Lipshits, ʿOded; Gadot, Yuval; Arubas, Benny; Oeming, Manfred (Eisenbrauns, 2017)
"The excavations at Ramat Rahel, just south of Jerusalem, revealed a complex of structures that existed for hundreds of years in which the Kingdom of Judah was a vassal of diverse empires. Over some 500 years, jars bearing seals were stored at the site. The findings throw new light on the late First Temple period and on most of that of the Second Temple. During these centuries Ramat Rahel was the administrative contact point between Judah and the ruling empires. This is what enabled independent Judean control of Jerusalem and the Temple, and the ability to maintain Jewis identity within Jerusalem almost without outside intervention and supervision. All this came to an end during the Hasmonean revolt."